(untitled) (Marketing Journal, 2025)
This article provides a theoretical analysis of improving the efficiency of investment projects in the automotive industry based on marketing research. The study systematically examines the impact of digital transformation, innovative marketing approaches, and consumer behavior on investment decision -making. Based on international experience, the role of marketing information in investment activities and its importance in project planning and evaluation are identified. The findings indicate that the use of marketing research helps reduce investment risks, improve the quality 576 of strategic decisions, and ensure the sustainable development of the automotive industry.